Contemporary American Artists (Mexico City : United States Embassy, 1992)
Alexander, Peter ; Ruscha, Ed ; Artschwager, Richard ; Chase, Louisa ; Dickson, Jane ; Marden, Brice ; Bartos, Adam ; Basquiat, Jean-Michel ; Bleckner, Rosa ; Borofsky, Jonathan ; Murray, Elisabeth ; Calder, Alexander ; Clay, Langdon ; Deutsch, David ; Hunt, Bryan ; etc.
Contemporary American Artists, Residence of Ambassador and Mrs. John D. Negroponte, Mexico City, Mexico 1990-1993
boek
Keywords: Amerika